Series solution with Frobenius method - Suad Mohammed Hassan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
T In this article we explained the structure of Frobenius method to solve a homogeneous linear differential equations of order two . In any homogeneous linear differential equations of order two we have three cases of two roots ( as a ,b ) of the indicial equation : Case1 : such that where is integer number and . Case 2 : . Case 3 : , such that . And we explained how to find the general solution of each case with many examples .